2008
DOI: 10.1111/j.1468-2982.2008.01589.x
|View full text |Cite
|
Sign up to set email alerts
|

Osmophobia in Juvenile Primary Headaches

Abstract: This study was planned to investigate the prevalence of osmophobia in juvenile headache sufferers and to analyse the diagnostic utility of osmophobia in order to distinguish migraine without aura from episodic tension-type headache. We examined 305 consecutive patients presenting at our Paediatric Headache Centre. A semistructured questionnaire was given to 275 selected patients affected by migraine or tension-type headache. The prevalence of osmophobia during attacks was 18.5%, mainly in migraine patients (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
62
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 38 publications
7
62
3
Order By: Relevance
“…Although osmophobia is not a diagnostic criterion for migraine, many studies show that this symptom is highly prevalent and is useful to differentiate migraine from tension-type headache [1,4,5,7,8,13]. Such as headache, osmophobia affects the quality of life of migraine patients and hinders the performance of their professional activities, especially in those who work in environments with strong odors, such as in perfumery, gas station and the selling of insecticide or beauty products [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although osmophobia is not a diagnostic criterion for migraine, many studies show that this symptom is highly prevalent and is useful to differentiate migraine from tension-type headache [1,4,5,7,8,13]. Such as headache, osmophobia affects the quality of life of migraine patients and hinders the performance of their professional activities, especially in those who work in environments with strong odors, such as in perfumery, gas station and the selling of insecticide or beauty products [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant association between odors and primary headaches, particularly to migraine with or without aura [1][2][3][4][5][6] and tension-type headache [1,[6][7][8]. The literature of its occurrence in secondary headaches is very scarce [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, we observed a severe intolerance to odours, pleasant or unpleasant, during headache attacks. 2,[4][5][6][7][8]10,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] However, a limited number of studies showed that odours may trigger headache attacks in some patients, particularly in migraineurs 1,3,6,7,9,24 and occasionally in cluster headache patients. 12,18 This intolerance to odours is known as osmophobia, and according to two studies that investigated osmophobia in secondary headaches, it occurred during headache attacks only in the primary headaches.…”
mentioning
confidence: 99%
“…2 Many researchers have confirmed that osmophobia is a symptom associated with migraine. 2,[4][5][6][7][8]10,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Despite such research, osmophobia is still not part of the diagnostic criteria for migraine. 34 In recent years, these studies were carried out in several countries.…”
mentioning
confidence: 99%